TEACHING TAMIL GRAMMAR FOR SECONDARY SCHOOL STUDENTS: AN EXPLORATION OF TEACHERS GRAMMAR CONTENT KNOWLEDGE - Seiyalu, Bavani Arumugam; Hamzah, Nurul Nazira; Kassim, Noorafini (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2025)
The lack of content knowledge among Tamil language teachers in secondary schools, particularly in the area of Tamil grammar, is an issue that has received limited scholarly attention. This gap underscores the need for research that provides a deeper understanding of teachers’ grammar content knowledge, especially in relation to morphology, within the context of Tamil grammar instruction. In response to this need, the present study aims to explore Tamil language grammar content knowledge in the teaching of Tamil grammar, drawing upon Shulman’s (1987) framework of pedagogical content knowledge. This study adopts a qualitative research approach employing a case study design. Five Tamil language teachers were selected through purposive sampling. Data were collected using semi-structured interviews and non-participant observation. The data, along with relevant documents, were analysed thematically using ATLAS. TI software (version 8.0). The validity and reliability of the findings were confirmed using several approaches, including the triangulation technique, member checks, peer review and expert verification techniques. The analysis was categorised under the identified central theme, morphology (colliyal). The findings indicate that Tamil language teachers possess a sound understanding of the Form Four Tamil grammar syllabus. They demonstrated proficiency in applying morphological grammar components such as i) ākupeyar; ii) uṭaṉpāṭṭuviṉai and etirmaṟaiviṉai iii) aṭai iv) pakupatam and pakāppatam and vii) yāppilakkaṇam. However, some Tamil language teachers exhibited uncertainty and inconsistencies in their interpretations, which occasionally diverged from the Secondary Integrated Curriculum (KSSM) Tamil grammar syllabus. In conclusion, this study contributes to the understanding of Tamil grammar content knowledge among secondary school teachers. The findings are expected to inform professional development initiatives and guide the Ministry of Education in strengthening Tamil grammar pedagogy and teacher expertise.